2011
DOI: 10.1080/19361521.2011.545048
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Loss in Children and Adolescents

Abstract: Although different types of childhood trauma have many common characteristics and mental health outcomes, traumatic loss in children and adolescents has a number of distinctive features. Most importantly, youth who experience a traumatic loss may develop childhood traumatic grief (CTG), which is the encroachment of trauma symptoms on the grieving process and prevents the child from negotiating the typical steps associated with normal bereavement. This article discusses the distinctive features of CTG, how it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 34 publications
1
33
0
2
Order By: Relevance
“…Many children and adolescents experience loss and bereavement (Mannarino and Cohen 2011). However, evidence suggests that poor minority youth are particularly likely to suffer the death of a loved one and may be at increased risk of complicated grief as a result of the nature of the loss.…”
Section: Loss and Grief Among African American Youthmentioning
confidence: 97%
See 1 more Smart Citation
“…Many children and adolescents experience loss and bereavement (Mannarino and Cohen 2011). However, evidence suggests that poor minority youth are particularly likely to suffer the death of a loved one and may be at increased risk of complicated grief as a result of the nature of the loss.…”
Section: Loss and Grief Among African American Youthmentioning
confidence: 97%
“…CTG occurs when a child loses a loved one under what they perceive as traumatic circumstances, develops trauma symptoms, and is unable to complete the normal grieving process (Mannarino and Cohen 2011;Cohen et al 2006). Traumatic grief most often accompanies deaths that are sudden or horrific but may also occur in response to a normal or expected death if the event is considered "unexpected, shocking, and terrifying" for the child (Cohen et al 2004b(Cohen et al , p. 1225.…”
mentioning
confidence: 97%
“…The proposed items span four primary conceptual domains and consist of (1) separation distress, including persistence of intense yearning, longing, sorrow, emotional pain, and preoccupation with the deceased person; (2) reactive distress and behavior in response to the death, including difficulty accepting the death, difficulty reminiscing about the deceased, and excessive avoidance of loss reminders; (3) disruptions in personal and social identity, including feeling like part of oneself has died with the deceased, which may begin as an acute personal existential crisis and develop over time into persisting impairment; and (4) preoccupation with the circumstances of the death, including distressing recollections of the circumstances of the death evoked by loss reminders (e.g., hearing the name of one's deceased father, or being in the company of his family of origin or friends, evokes distressing recollections of his death). These preoccupations may be especially pronounced when the death occurs under violent, gruesome, or otherwise tragic circumstances (Brown et al, 2008;Cohen, Mannarino, & Staron, 2006;Dillen et al, 2009;Layne et al, 2008;Mannarino & Cohen, 2011).…”
Section: Conceptual Domains Of Griefmentioning
confidence: 97%
“…Preoccupation with the circumstances of the death may manifest in children as reenacting the death through play or repetitive drawings of a particularly disturbing scene of the death. Reflecting ongoing preoccupation with the threat of similar future losses, reenactment or play may extend to efforts to prevent the future death of other loved ones (Eth & Pynoos, 1985;Mannarino & Cohen, 2011). Children may have repetitive fantasies characterized by themes of prevention, protection, and repair (counterfactual thinking) in which they imagine what they or others might have done to prevent the death, intervene effectively, or repair fatal injuries.…”
Section: Criterion Bmentioning
confidence: 97%
“…Grieving children are at higher risk for experiencing traumatic grief (Mannarino & Cohen, 2011;McClatchey, Vonk, & Palardy, 2009), decreased school performance (Balk & Corr, 2009), and lower self-esteem (Haine, Ayers, Sandler, & Wolchik, 2008) than their nonbereaved peers. In April 2012, the National Alliance for Grieving Children released a national poll of bereaved children and teenagers (N = 531) and found that sadness was most pervading emotion felt by 75% of the respondents.…”
Section: Why Offer a Residential Grief Camp?mentioning
confidence: 99%